Communication System In The HealthyEnvironment In Algeria - belabes, taqieddine; yahia, takieddine (Journal of Social Sciences and Humanities, 2021)
The birth of the systemic approach resulted in an epistemological revolution that changed the foundations and concepts of several disciplines, and had the greatest impact on the first linear communicative models, which were considered by the pioneers of the Palo Alto School of Systematic Communication as models that were not worthy of intellectual attention and did not rise to the explanation of the communicative phenomenon. The emergence of the second suggestive (cybernetics) in the middle of the twentieth century clearly contributed to the science of programming as the foundations for controlling living organisms and machines and studying the communicative methods between them, relying on linearly controlled mathematical rules and physiochemical systems. Such as physics, biochemistry and mathematics, until the development of this systemic thought in the beginning of the seventies and the development of a new perspective for the study of social systems of institutions and organizations, surpassing in that solid celestial mechanics and coalesced within the flexible human sciences. The systemic approach took a different direction in the analysis and interpretation of social systems as a unified, interactive format, and focused on the dismantling and fragmentation of the communication process according to its positioning and interaction, and adopted it as an open system in which all the actors participate within a specific context and an appropriate environment that allows the circular coordination interaction to reach all participants in the communication process The system of communication imposed itself on the therapeutic healthy environment from the beginning, and communication was the basis of a healthy social construction at that time, In this cognitive study, we address the “communication system in the healthy environment in Algeria” through the intellectual and epistemological projection of the systemic approach and its birth, and the Palo Alto School of Communication adopts this approach through the efforts of anthropological researchers such as GREGORY BATESON and Watzlawik in the birth of a healthy therapeutic systemic communication approach. Key words: Systematic Thought, Systematic Approach, System of Communication, Healthy Environment, Palo Alto School of Communication, Cybernetics . - Abstract in French : La naissance de l'approche systémique a abouti à une révolution épistémologique qui a changé les fondements et les concepts de plusieurs disciplines, et a eu le plus grand impact sur les premiers modèles de communication linéaire, qui ont été considérés par les pionniers de l'école de Palo Alto de la communication systématique comme des modèles qui n'étaient pas dignes d'attention intellectuelle et n'ont pas suscité l'interprétation du phénomène communicatif. L'émergence du second suggestif (cybernétique) au milieu du XXe siècle a clairement contribué à la science de la programmation comme base pour contrôler les organismes vivants et les machines et étudier les méthodes de communication entre eux, en s'appuyant sur des règles mathématiques contrôlées linéairement et des systèmes physicochimiques. Tels que la physique, la biochimie et les mathématiques, jusqu'au développement de cette pensée systémique au début des années soixante-dix et le développement d'une nouvelle perspective pour l'étude des systèmes sociaux des institutions et des organisations, dépassant dans cette solide mécanique céleste et fusionnée dans les flexibles sciences humaines. L'approche systémique a pris une direction différente dans l'analyse et l'interprétation des systèmes sociaux en tant que format unifié et interactif, et s'est concentrée sur le démantèlement et la fragmentation du processus de communication en fonction de son positionnement et de son interaction, et l'a adoptée comme un système ouvert dans lequel tous les acteurs participent dans un contexte spécifique et un environnement approprié qui permet à l'interaction de coordination circulaire d'atteindre tous les participants au processus de communication. Le système de communication s'est imposé dès le début à l'environnement thérapeutique sanitaire et la communication était à l'époque la base d'une construction sociale saine. Dans cette étude cognitive, nous abordons le «système de communication dans un environnement sain en Algérie» à travers la projection intellectuelle et épistémologique de l'approche systémique et sa naissance, et l'École de communication Palo Alto adopte cette approche grâce aux efforts de chercheurs anthropologues tels que GREGORY BATESON et WATZLAWIK dans la naissance d'une approche de communication systémique thérapeutique sanitaire. Mots clés: Pensée systématique, approche systématique, système de la communication, environnement sanitaire, école de communication de Palo Alto, cybernétique